Analysis Of Maf'ul Bih And Maf'ul Mutlaq In Surah Al-Kahfi And The Learning Model - Safitri, Siti Nurul Anjani; Hapsari, Ameilia Frida Putri; Fadil, Muhamad Zainul; Azura, Wulan Annisa; Faida, Farah (DAS Institute, 2023)
This research aims to find maf’ul mutlaq and maf’ul bih in the Al-Quran Surah Al-Kahf, as well as find the appropriate learning model. The method used is a qualitative method with the type of library research. Data analysis in this research used the Milles and Huberman technique. Based on data analysis in Surah Al-Kahf, there are 43 maf’ul mutlaq and 80 maf’ul bih and the number of maf’ul bih is greater than maful mutlaq because it includes isim 'umdah which is needed in a sentence structure.